1991
DOI: 10.1111/j.1432-1033.1991.tb15872.x
|View full text |Cite
|
Sign up to set email alerts
|

Determination of disulfide bridges in natural and recombinant insect defensin A

Abstract: The primary-structure comparison of natural insect defensin A from Phormia terranovae and recombinant insect defensin A from Saccharomyces cerevisiae has been accomplished using a combination of Edman degradation and liquid secondary ion mass spectrometry. The natural and recombinant proteins have the same primary structure with identical disulfide-bond designations (Cys3 Cys30, Cysl6 Cys36 and Cys20 Cys38) as determined from the peptides obtained after thermolysin digestion. The combined use of Edman degradat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

1992
1992
2000
2000

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 16 publications
0
22
0
Order By: Relevance
“…Interestingly, moricin has no modified amino acid residues such as the ␣-amidation of C termini in cecropins, the hydroxylation of Lys residues in B. mori cecropins, the O-glycosylation of Thr residues in proline-rich antibacterial peptides (Bulet et al, 1993;Cociancich et al, 1994b;Hara and Yamakawa, 1995), or formation of intramolecular disulfide bonds in defensins (Kuzuhara et al, 1990;Lepage et al, 1990). These unique properties of moricin provide a favorable condition for the production of the peptide by chemical synthesis or by biotechnology using suitable protein expression vectors.…”
Section: Table III Effect Of the Novel Peptide On Viability Of S Aurmentioning
confidence: 99%
“…Interestingly, moricin has no modified amino acid residues such as the ␣-amidation of C termini in cecropins, the hydroxylation of Lys residues in B. mori cecropins, the O-glycosylation of Thr residues in proline-rich antibacterial peptides (Bulet et al, 1993;Cociancich et al, 1994b;Hara and Yamakawa, 1995), or formation of intramolecular disulfide bonds in defensins (Kuzuhara et al, 1990;Lepage et al, 1990). These unique properties of moricin provide a favorable condition for the production of the peptide by chemical synthesis or by biotechnology using suitable protein expression vectors.…”
Section: Table III Effect Of the Novel Peptide On Viability Of S Aurmentioning
confidence: 99%
“…This mass spectrum also contains two large peaks at mlz 565.0 and at mlz 1678.4 that we interpreted as fragments obtained from a tryptic peptide after rupture of an interchain disulfide bond. It has been shown that peptides consisting of two chains linked by a disulfide bridge undergo, in LSIMS, an intense fragmentation at the disulfide bridge which generates an [M+H]+ ion for each peptide chain [16]. (----) show all tryptic identified peptides ; the fragments marked with a full line ( -) show peptides identified after endoproteinase Glu-C cleavage.…”
Section: Endoproteinase Glu-cmentioning
confidence: 99%
“…From the known sequence of the CHH, one can predict which peptide could be generated by endoproteinase Glu-C digestion and only one solution was possible to explain the spectrum of the peptide from peak 6 [16]. One chain would be SCLKD (peptide 51-55; expected mass 564.2 Da) and the other DCYNLYRKPHVAAE (peptide 25 -38 ; expected mass 1677.8 Da).…”
Section: Endoproteinase Glu-cmentioning
confidence: 99%
“…From these triply and doubly protonatcd ions, the molccular mass of the fragment was deduced to correspond to 1558.6 Da. A computer program [16] was used to predict the molecular masses of all possible cleavage products which could be obtained with all theoretically possible combinations of disulfide bridges within the pcptidc. This program includes clcavages at all 37 peptides bonds of the antibacterial peptide and not only at the expected enzymic cleavage sites mentioned above.…”
Section: Determination Of Disulfide Bondsmentioning
confidence: 99%